Physiological stress of basketball referees during a national competition - Ramiro Marques Inchauspe; Pablo Morales Barbian; Gregório Aguiar Lélis; Flávia Renata de Almeida; Alejandro Vaquera (Universidade Federal de Santa Catarina, 2021)
The aim of this study was to examine the physiological demands of seven referees during a national basketball competition. During each of the tournament matches, heart rate (HR), relative exercise intensity as a percentage of age - predicted maximum HR (HRmax), proportion of playing time within the exercise intensity categories defined by the ACSM were recorded for each referee in each period and the entire game. There were no significant differences between periods for any variable. Referees, using a format of three referees per match, worked with an average HR of 150 bpm (range 110-181 bpm) for each quarter of the match, which equals a relative intensity> 70% of HRmax for most (∼76%) for each quarter. Other studies will assist in developing appropriate training programs for elite basketball referees to maintain and / or maximize performance.